HISTOCHEMICAL CHARACTERISTICS OF PLACENTAS PARTURIENTS WHO GAVE BIRTH TO INFANTS WITH CONGENITAL MALFORMATIONS - Seidbekova, F.O. (World of Medicine and Biology, 2012)
Histochemical studies in the connective tissue of placenta showed inhibition of redox enzymes, decreased markers of ATP-ase activity, reducing the capacity of non-specific phosphatases. These changes have shown that the placenta is fully its function does not and can not adequately ensure the growth and development of the fetus.